Educação ambiental e políticas públicas nas dissertações e teses de educação ambiental no Brasil: análise dos processos de elaboração e implementação - Nery-Silva, Ana Clara [UNESP] (2015)
Seeking to investigate public policies related with environmental education, this state of the art research had as the object of investigation dissertations and theses contained in the catalog of the project A EDUCAÇÃO AMBIENTAL NO BRASIL: análise da produção acadêmica (dissertações e teses) named like Project EARTE too. Twenty-four research sorted in the 'Public policies in EA' Study's theme were found, focused on elaborating and implementing of these policies. The productions were contextualized in the most general context of the environmental education research and, after, a new thematic focus was done, prioritizing just five investigations focused in the federal levels. These surveys were analyzed using Content Analysis framework (Bardin, 2011). We sought to answer the following research questions: is possible to find indications about elaborating and implementing process of public policies as a research object in these productions? If this can be found, what political agents/actors and sociopolitical contexts are referenced in these productions? What concepts of environmental education and public policy are present in these theses and dissertations ? The political agents/ actors held responsible for the elaboration and implementation of public policies were organized in two categories (governmental and nongovernmental), totalizing eleven different agents/ actors. Public policy conceptions approached this as being in a dependency of the official authorities (governments and states), emphasizing, although the necessity about a participatory management in public policies related to environmental education. About the sociopolitical contexts, was found the necessity to understand the different action strategies of the different sociopolitical agents/ actors who act in the institutionalization process and the interests involved in this stages. Environmental education concepts found were connected to the three...